Walkability and attachment to tourism places in the city of Kuala Lumpur, Malaysia - Ujang, Norsidah; Muslim, Zulkifli (The Tourism Research Unit of The Athens Institute for Education and Research, 2015)
Tourism places as the main income generating areas should be highlighted as tourist-friendly places. Walkable tourism places will intensify the tourist magnets and focal elements that may increase place attachment. Visitors which include tourists have intensively used urban places, facilities and services, but little of these spaces were designed specifically for tourists’ use. In view of the lack of concern as to how to provide quality and memorable walking experience for visitors, this study identifies issues regarding walkability and pedestrians’ experience of tourism places in the city of Kuala Lumpur, Malaysia. This paper presents visitors’ feedback on walkability of the city in light of place attachment dimensions. It analyses visitors’ satisfaction and attachment gathered from preliminary surveys and interviews conducted in several places of attractions in the city. The preliminary findings indicate that pleasantness while walking, and the accessibility affects the visitors’ form of engagement with activities and the functional attachment to the places. The emotional attachment is also reflected in the visitors’ identification of visual attractiveness that reflects image and identity, particularly in the areas with strong historical and cultural attributes.